New nano biomaterials inspired by biomechanics - Yang, Lei (Henry Stewart Talks, 2015)
Role of Mechanics in Biology, What is Biomechanics?, New Era of Biomaterials Engineering, Design of Nanomaterial Topographical Guidance to Regulate Cell Functions, Thermodynamically Inspired Nanocrystalline Diamond (NCD) for Controlling Cell Spreading
Archived at 2023/05/31